Linking Chlorophyll Concentration and Wind Patterns Using Satellite Data in the Central and Northern California Current System - Stone, Hally B.; Banas, Neil S.; MacCready, Parker; Kudela, Raphael M.; Ovall, Bridget (Frontiers in Marine Science, 2020)
The California Current System (CCS) is a highly productive region because of wind-driven upwelling, which supplies nutrients to the euphotic zone. Numerous studies of the relationship between phytoplankton productivity and wind patterns suggest that an intermediate wind speed yields the most productivity on the shelf. However, few studies have considered the productivity-wind relationship across the entire CCS, including the Northern CCS (north of 42°N), an unusually productive region with highly variable upwelling- and downwelling-favorable winds. Using satellite chlorophyll concentration from GlobColour together with QuikSCAT and ASCAT winds, we examine the relationship between shelf (shallower than the 150 m isobath) chlorophyll concentration and wind patterns in the Central and Northern CCS. Results from this empirical analysis suggest that while there is a dome-shaped relationship between mean chlorophyll concentration and wind stress for the whole system, the Central CCS and Northern CCS have significantly different relationships, which is evident in the separation between their mean chlorophyll concentration-wind stress curves. The Northern CCS also supports high chlorophyll concentration during downwelling-favorable winds. To understand this difference in chlorophyll concentration-wind stress relationships, results from particle tracking experiments using a ROMS model of the Northern CCS are used to map shelf retention times with respect to wind patterns. These results suggest that on the 1°-latitude scale, the effect of wind intermittency on retention is minimal in the Northern CCS; however, this result does not disqualify the influence of more complex controls on retention like wind intermittency on smaller spatial scales. Lastly, we present a revised hypothesis to describe the relationship between chlorophyll concentration and wind stress in the CCS that includes the influence of non-upwelling-derived nutrients in the Northern CCS.